Pilot study on the effect of a Meditation–Mindfulness–Positive Psychology Training program on perceived stress and mental well-being in Korean nursing students: A mixed methods analysis - Young Im Cho; Hyo Jin Kim; Dong Hee Kim (PLoS ONE, 2026)
Nursing students experience stress that negatively affects their mental well-being and academic performance. Conventional mindfulness-based interventions are too long to fit the students’ demanding schedules. This study aimed to examine the feasibility and preliminary effectiveness of an adapted Meditation–Mindfulness–Positive Psychology Training (MMPT) program tailored to nursing students’ needs. The program was designed as to be shorter, to be conducted online, and to be tailored to the needs of nursing students. A mixed-methods pilot study was conducted among junior and senior nursing students in Korea. The experimental group participated in a six-session online MMPT program into which meditation, mindfulness, gratitude journaling, and self-compassion practice were incorporated. Quantitative outcomes were assessed before and after intervention. Qualitative data were collected through in-depth interviews and analyzed through inductive content analysis. The quantitative results showed significant improvements in gratitude disposition, self-compassion, and perceived stress, but not in mindfulness or overall mental health. Qualitative findings complemented these results by revealing perceived improvements across all target domains, with participants reporting enhanced calmness, greater self-kindness, increased positivity, and stronger coping strategies. Students highlighted the value of gratitude journaling, compassion-based exercises, and supportive peer interactions, which reinforced their engagement and sense of belonging. The MMPT program adapted for this study demonstrated feasibility and preliminary effectiveness in reducing stress and enhancing positive psychological resources among nursing students. By integrating mindfulness and positive psychology into a brief and accessible format, this study underscores the theoretical and practical value of needs-based interventions for supporting nursing students’ well-being. Further large-scale and longitudinal studies are warranted to validate and extend these findings.